2017
DOI: 10.1101/126813
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Slow conformational exchange and overall rocking motion in ubiquitin protein crystals

Abstract: Proteins perform their functions in solution but their structures are most frequently studied inside crystals. Here we probe how the crystal packing alters microsecond dynamics, using solid-state NMR measurements and multi-microsecond MD simulations of different crystal forms of ubiquitin. In particular, near-rotary-resonance relaxation dispersion (NERRD) experiments probe angular backbone motion, while Bloch-McConnell relaxation dispersion data report on fluctuations of the local electronic environment. These… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(64 citation statements)
references
References 66 publications
1
63
0
Order By: Relevance
“…Higher quality data also might be needed to substantially improve the model. Recent solid-state NMR (ssNMR) experiments combined with crystalline protein simulations (Kurauskas et al, 2017;Ma et al, 2015;Mollica et al, 2012) create opportunities for joint validation of MD simulations using crystallography and NMR. An ssNMR + MD study of the protein GB1 (Mollica et al, 2012) showed reasonable agreement between 200 ns MD simulations and the data for longitudinal relaxation rates and chemical shifts, with lower agreement for the transverse relaxation rates.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Higher quality data also might be needed to substantially improve the model. Recent solid-state NMR (ssNMR) experiments combined with crystalline protein simulations (Kurauskas et al, 2017;Ma et al, 2015;Mollica et al, 2012) create opportunities for joint validation of MD simulations using crystallography and NMR. An ssNMR + MD study of the protein GB1 (Mollica et al, 2012) showed reasonable agreement between 200 ns MD simulations and the data for longitudinal relaxation rates and chemical shifts, with lower agreement for the transverse relaxation rates.…”
Section: Figurementioning
confidence: 99%
“…An ssNMR + MD study of the protein GB1 (Mollica et al, 2012) showed reasonable agreement between 200 ns MD simulations and the data for longitudinal relaxation rates and chemical shifts, with lower agreement for the transverse relaxation rates. An ssNMR + MD study of ubiquitin (Kurauskas et al, 2017;Ma et al, 2015) attributed the transverse relaxation rates to rigid-body rotations of whole proteins in the crystal lattice, with amplitudes of 3-5 extracted from the simulations. To assess the importance of rigid-body rotations in the present staphylococcal nuclease simulation, snapshots of each of the 32 copies of the protein were rotationally aligned with a reference structure (x2).…”
Section: Figurementioning
confidence: 99%
“…Ubiquitin is a convenient model system, because its μ s dynamics has been characterized extensively by solution‐NMR, solid‐state NMR and MD simulations ,,. The exchange process involves a flip of the peptide plane of D52/G53, along with reorientation of the side chain of E24, which is H‐bonded in one of these two states, but not in the other state.…”
Section: Resultsmentioning
confidence: 99%
“…As an important consequence of this dependence on the spectral density function at sums and differences of ω1 and ωMAS , in the presence of μ s motion, an increase of R 1ρ is observed as the RF field strength and the MAS frequency become similar. This effect, described by Redfield theory, and shown in several studies,, was dubbed “NEar‐Rotary Resonance RelaxationDispersion” (NERRD) recently . We use this term throughout this manuscript.…”
Section: Introductionmentioning
confidence: 99%
“…We did so for several dynamics studies and compared the result to the reported τ c values. The biasing/reported τ c for a number of studies are: HET‐s(218–289) 15 N 17 μs/19 μs, HET‐s(218–289) 13 C α 11 μs/7 μs, ubiquitin (2‐methyl‐2,4‐pentanediol (MPD) crystallization) 2.1 μs/1.5 μs (median value), ubiquitin (PEG crystallization) 26 μs/20 μs (SI, Figure 5) . The good agreement between these numbers suggests that the real motion is too complex to be described with a mono‐exponential correlation function, so that results bias to where the experiments are sensitive.…”
Section: Figurementioning
confidence: 96%